The midpoint of these two points is (-1, 8).
In order to find the midpoint, you must take the average of each part of the coordinates. You do this by adding them together and dividing by 2. We'll start with the x-coordinates.
(-1 + -1)/2 = -1
Now we'll use the y-coordinates.
(10 + 6)/2 = 8
This gives us the ordered pair of (-1, 8)
Answer:
32 5/8 (or 32 and 5/8)
Step-by-step explanation:
Okay, so this problem is asking for us to solve this problem with the substitution of a variable: x = -4. Before we fully solve this problem, we need to replace all of those x variables with -4 so that it is easier to solve.
-7 1/4(-4) + 3 5/8.
To make this problem even easier to solve, let's turn these mixed numbers into improper fractions. To do this, multiply the denominator by the whole number. Then add the numerator to this number. The new number that you just got is now your new numerator for this number.
-29/4(-4) + 3 5/8.
Repeat the last step to turn the other mixed number into an improper fraction.
-29/4(-4) + 29/8.
Now let's multiply that -4 by 29/4. Because a whole number technically has a denominator of 1, we can now set up the next part of our problem. (The symbol * means multiplication since we can't use x since it is already being used as a variable in this equation.)
(-29/4 * -4/1) + 29/8.
29 + 29/8.
Now to solve the rest of this problem, let's convert the whole number of 29 so that it has a denominator of 8. This is that these two numbers are addable.
<u>29</u> x <u>8</u> = <u>232</u>
1 x 8 = 8
Now these numbers are addable. So:
232/8 + 29/8 = 261/8 = 32 5/8.
I hope that this helps.
Step-by-step explanation:
Shortest way to solve this question is to find the factors of the given expression.
The given expression is (x² + 13).
Now we have to factorize it.
(x² + 13) = x² + (√13)²
= x² + [-(i)²√(13)²] [Since i = √(-1)]
= x² - (i√13)²
= (x - i√3)(x + i√3) [Since (a² - b²) = (a + b)(a - b)]-by-
It'd be the first one.
Look at it like this:
3x2=6
6x2=12
12x2=24
24x2=48
48x2=96
96x2=192